Veterinary parasitology reference manual - Foreyt, Bill. (Ames, Iowa : Iowa State University Press, 2001)
Veterinary Parasitology Reference Manual, Fifth Edition is a practical, thorough, bench top reference for basic diagnostic veterinary parasitology. The manual provides pertinent information on parasite life cyles, importance, location in the host, zoonotic potential, current literature, diagnosis, and treatment. It also includes step-by-step instructions for the most common diagnostic procedures used in routine veterinary practice. Sections are organized by animal host species, including dogs; cats; cattle, sheep and goats; llamas; horses; pigs; birds; ratites (ostriches, emus, and cassowaries); and laboratory animals, as well as wildlife, reptiles, marine mammals, and humans. There is a section in which common artifacts found in fecal samples are presented, and the last section includes conversion tables and a list of abbreviations.
Sect. 1. Diagnostic Parasitology -- Sect. 2. General Parasitology -- Sect. 3. Parasites of Dogs -- Sect. 4. Parasites of Cats -- Sect. 5. Parasites of Cattle, Sheep, and Goats -- Sect. 6. Parasites of Llamas -- Sect. 7. Parasites of Horses -- Sect. 8. Parasites of Pigs -- Sect. 9. Parasites of Birds -- Sect. 10. Parasites of Ratites (Ostriches, Emus, and Cassowaries) -- Sect. 11. Parasites of Laboratory Animals -- Sect. 12. Parasites of Wildlife -- Sect. 13. Parasites of Marine Mammals -- Sect. 14. Parasites of Reptiles -- Sect. 15. Parasites of Humans -- Sect. 16. Common Artifacts in Feces -- Sect. 17. Tables...
Includes bibliographical references and index.
Keywords: Parasites; Parasitic Diseases, Animal; Veterinary parasitology -- Handbooks, manuals, etc; Handbook; Handbooks and manuals